Diel variation in zooplankton assemblages around Aceh Island, Pahang, Malaysia - AIN BATRISYIA BINTI MOHD ZAMANY; SUN MENXIA; MOHAMAD AMIR AIMAN ABDULLAH; AZMAN ABDUL RAHIM (Biodiversitas Journal of Biological Diversity, 2025)
Abstract. Zamany ABBM, Menxia S, Abdullah MAA, Rahim AA. 2025. Diel variation in zooplankton assemblages around Aceh Island, Pahang, Malaysia. Biodiversitas 26: 4685-4693. This study investigated diel fluctuations in zooplankton distribution, composition, and abundance in the coastal waters off Aceh Island, Pahang, Malaysia. Sampling was conducted on 24 April 2025 during the dry season, using standardized net tows at five fixed stations during both day and night, with three replicates per station. A total of 54 taxa were identified at night and 49 during the day, with copepods consistently dominating the assemblages—accounting for 97.06% of nocturnal and 80.4% of diurnal abundance. Euterpina sp. 1 was the most frequently encountered copepod across both periods. Zooplankton densities ranged from 131.68 to 220.60 ind/m³ (n = 6,178) during the day and 165.2 to 239.0 ind/m³ (n = 11,995) at night. Diversity metrics, including Shannon-Wiener (H’) and Pielou’s evenness (J’), indicated moderate to high diversity, with greater species richness and evenness observed during nocturnal sampling, particularly at deeper sites (STN 1 and STN 4). These patterns align with existing records from adjacent waters in Pahang and Johor, where copepods consistently dominate the zooplankton community. The study highlights the importance of incorporating diel sampling into biodiversity monitoring, as single-time-point surveys may underestimate community diversity and overlook diel behavioural dynamics such as vertical migration. These findings contribute to the growing baseline data needed for effective ecological assessments and conservation efforts in Malaysian coastal ecosystems.